Water-use characteristics of Syzygium antisepticum and Adinandra integerrima in a secondary forest of Khao Yai National Park in Thailand with implications for environmental management - Ampornpitak, Ratchanon; Nathalang, Anuttara; Tor-ngern, Pantana (PeerJ, 2023)
Background Southeast Asia has experienced widespread deforestation and change in land use. Consequently, many reforestation projects have been initiated in this region. However, it is imperative to carefully choose the tree species for planting, especially in light of the increasing climate variability and the potential alteration of plantation on the watershed water balance. Thus, the information regarding water-use characteristics of various tree species and sizes is critical in the tree species selection for reforestation. Methods We estimated tree water use (T) of dominant species including Syzygium antisepticum and Adinandra integerrima, hereafter Sa and Ai, respectively, in a secondary tropical forest in Khao Yai National Park, Thailand, using sap flow data, and compared T between species and size classes. Additionally, we evaluated the responses of T of both species in each size class to environmental factors including soil moisture and vapor pressure deficit (VPD). Results Results showed consistently higher T in Sa compared to Ai across ranges of VPD and soil moisture. Under low soil moisture, T of Sa responded to VPD, following a saturating exponential pattern while Ai maintained T across different VPD levels, irrespective of tree size. No responses of T to VPD were observed in either species when soil water was moderate. When soil moisture was high, T of both species significantly increased and saturated at high VPD, albeit the responses were less sensitive in large trees. Our results imply that Ai may be suitable for reforestation in water-limited areas where droughts frequently occur to minimize reforestation impact on water availability to downstream ecosystems. In contrast, Sa should be planted in regions with abundant and reliable water resources. However, a mixed species plantation should be generally considered to increase forest resilience to increasing climate variation.
Keywords: Tree water use; Secondary forests; Syzygium antisepticum; Adinandra integerrima; Tropical forests; Sap flow